Operative Treatment of Acute Distal Femur Fractures: Review of literature - Zandi, Reza; Minator Sajjadi, Mohammad Reza; Okhovatpour, Mohammad Ali; Sadighi, Mehrdad; Ebrahimpour, Adel; Jalalpour, Pooyan (Researcher Bulletin of Medical Sciences, 2020)
Fractures of the distal femur may be extra articular or have an intra articular component. Mismanagement of any of these fractures can result in abnormalities of alignment of the load-bearing axis of lower limb and/or rotational deformities. Essentially all supracondylar femur fractures require operative intervention because of the severe potential risks of prolonged bed rest. Yet, despite their proven track record and benefits over older implants, technical errors are common and must be overcome with proper preoperative planning and intra-operative attention to details. The goal of this study was to present an update on the management of these fractures